[Suriname] Government policy statement 1988-1993 - Shankar, R. ([Government of Suriname] ParamariboSR, 1988)
Outlines the Suriname government's plans and policies with regards to finance and economics; education, science and culture; domestic and foreign affairs; the press; the judicial system; the international drug problem; taxation; foreign currency management; infrastructure; agriculture; mining; natural resources; employment and healthcare.